The prion-like transmission of tau oligomers via exosomes - Jackson, Noel A.; Guerrero-Muñoz, Marcos J.; Castillo-Carranza, Diana L. (Frontiers in Aging Neuroscience, 2022)
The conversion and transmission of misfolded proteins established the basis for the prion concept. Neurodegenerative diseases are considered “prion-like” disorders that lack infectivity. Among them, tauopathies are characterized by the conversion of native tau protein into an abnormally folded aggregate. During the progression of the disease, misfolded tau polymerizes into oligomers and intracellular neurofibrillary tangles (NFTs). While the toxicity of NFTs is an ongoing debate, the contribution of tau oligomers to early onset neurodegenerative pathogenesis is accepted. Tau oligomers are being transferred from neuron to neuron propagating through the brain inducing neurodegeneration. Recently, transmission of tau oligomers via exosomes is being proposed. There is still too much to uncover about tau misfolding and propagation. Here we summarize novel findings of tau oligomers transmission and propagation via exosomes.